2022
DOI: 10.18632/aging.204156
|View full text |Cite
|
Sign up to set email alerts
|

Integrated proteomics and metabolomics analysis reveals hubs protein and network alterations in myasthenia gravis

Abstract: Background: Thymoma-associated myasthenia gravis (TAMG) is a well-described subtype of Myasthenia gravis (MG). Nevertheless, the detailed proteins and bioprocess differentiating TAMG from TAMG (−) thymoma have remained unclear. Methods: The proteomics and metabolomics were carried out on serum samples from thymoma group ( n = 60, TNMG), TAMG (+) thymoma group ( n = 70, TAMG (+)), and TAMG (−) thymomas group ( n = 62, TAMG (−)), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…IPA was significantly downregulated in class 1 (20 thymoma and 1 TC) compared with class 2 (12 thymic hyperplasia) ( p < 0.05, Figure 5A). Thymoma is often associated with autoimmune diseases, especially MG 20 . Studies have shown that 10–20% of MG patients develop thymoma and ca 30% of thymoma is associated with MG 22 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…IPA was significantly downregulated in class 1 (20 thymoma and 1 TC) compared with class 2 (12 thymic hyperplasia) ( p < 0.05, Figure 5A). Thymoma is often associated with autoimmune diseases, especially MG 20 . Studies have shown that 10–20% of MG patients develop thymoma and ca 30% of thymoma is associated with MG 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Thymoma is often associated with autoimmune diseases, especially MG. 20 Studies have shown that 10-20% of MG patients develop thymoma and ca 30% of thymoma is associated with MG. 22 To investigate if the identified differential metabolic features had significant abundance changes between thymoma with and without MG, we analyzed their normalized abundance in TAMG (n = 10) and thymoma and 1 TC without MG (n = 11) samples. Tryptophan level in the TAMG group was found to be significantly lower than that in the MG(À) thymoma and TC group (Figure 5B), whereas the 9-decenoylcarnitine level was significantly higher (Figure 5C) (p < 0.05).…”
Section: Metabolic Features That Are Differentially Abundant In Tamg ...mentioning
confidence: 99%
See 3 more Smart Citations